TINGKAT DEPRESI BERHUBUNGAN DENGAN STATUS KESEHATAN TETAPI TIDAK DENGAN STATUS GIZI LANSIA DI KARAWANG - Elvandari, Milliyantri; Rahmatunisa, Risma; Sefrina, Linda Riski (Lembaga Penerbitan Unversitas Esa Unggul, 2019)
The purpose of this study was to analyze the relationship between depression levels, nutritional status and elderly health status at Karawang. This type of research was observational with a cross sectional study conducted in July 2018 with a total subject of 50 people (total sampling), using instructional questionnaires (elderly nutritional status, disease history, level of depression) and measurement of nutritional status. Analyze by chi-square. The results obtained showed that there was a correlation between depression level and health status (p = 0,000), and there was no correlation between nutritional status and elderly health status (p = 0,708).Â Keywords: elderly, nutritional status, level of depression, health status